Endolymphatic Hydrops in Patients With Intralabyrinthine Schwannomas - Zhang, Yibo; Li, Feitian; Dai, Chunfu; Wang, Wuqing (Frontiers in Surgery, 2021)
Purpose: The presence of endolymphatic hydrops (EH) in patients with intralabyrinthine schwannomas (ILSs) is poorly understood. This study aims to determine whether there is a correlation between endolymphatic hydrops and clinical presentations of ILS. Methods: Data from nine patients with ILSs were retrospectively reviewed between 2007 and 2020. Temporal bone MRI with intratympanic or intravenous injection of gadolinium was applied to detect ILSs and EH. Results: 3D real inversion recovery (IR) sequence MRI of the temporal bone confirmed ipsilateral EH in four patients (4/6). All four patients with EH on MRI presented with vertigo similar to Meniere's disease. Among these patients with EH, one patient with EH in the cochlea showed moderate sensorineural hearing loss, while three patients with EH in both the vestibule and cochlea showed profound hearing loss. MRI demonstrated a transmacular tumor (TMA) in one patient, intravestibular (IV) in four patients, and vestibulocochlear (VC) in four patients. Two IV cases showed moderated hearing loss, while the TMA and VC cases showed profound hearing loss. Transotic resection of the tumor was applied in five patients; translabyrinthine resection was applied in one patient; two patients were under observation; and one patient was given intratympanic injection of gentamicin (ITG). During follow-up, all of the treated patients reported relief of vertigo, and postoperative MRI was performed in two patients, which showed no tumor recurrence. The two patients under observation showed no deterioration of hearing loss or vertigo. One patient was lost to follow-up. Conclusion: EH concurrent with ILSs has been underestimated previously. With the extensive application of temporal bone MRI paradigms, such as 3D-real IR sequence MRI, more cases of potential EH in patients with ILS will be identified. The severity of hearing loss may be associated with the location of the tumor and the degree of EH.